A Possible Twin: The 1960s Twin Study Revisited/Twin Research: Twin-to-Twin Heart Transplantation; Distinguishing Monozygotic Twins; Twin Conceptions via Oocyte Donation; Factors Affecting Craniofacial Traits/In the Media: Triplet Delivery in the UK; Conjoined Twins and the Concept of Self; Colombian Twin Trainers; Skin Grafting to Save an Identical Co-Twin; Lack of Physical Flaws in Dolly the Cloned Sheep; Possible Conjoined Twins of Opposite-Sex; Passing of the Remaining Twin From the World's Longest Separated Pair. (15th March 2018) - Segal, Nancy L.
Abstract : This article begins with the story of a 51-year-old Los Angeles, California man, Justin Goldberg, whose daughter caught a glimpse of his striking look-alike at a popular market. Many people have so-called doppelgängers, but this occurrence is especially intriguing — the individual in question, born in New York City in the mid-1960s to an unwed mother, was an adoptee placed by the Louise Wise Adoption Agency. This agency, under the guidance of a prominent psychiatrist, decided to place twins in separate homes. Some of these twin children were part of a controversial child development study that was hidden from them and their parents. Next, recent and current twin research on heart transplantation, distinguishing monozygotic co-twins, twin conceptions via oocyte donation and factors affecting craniofacial traits are summarized. The article concludes with highlights on twins in the media, specifically, a triplet delivery in the United Kingdom, self-concept and consciousness in conjoined twins, Colombian twin trainers, skin grafting to save an identical co-twin, lack of physical flaws in Dolly the cloned sheep, possible opposite-sex conjoined twins, and the passing of the remaining twin from the world's longest separated pair.